The Factoring Contract and Its Modalities - ALDEIA, Susana Rodrigues (Revista Jurídica Portucalense, 2025)
This article examines the various types of factoring contracts, an essential financial tool for companies seeking liquidity and financing solutions. The study looks at the historical evolution of factoring, its financing and guarantee functions, and the issue of notifying the debtor. In addition, specific modalities such as factoring with and without recourse, domestic and international factoring, and other variants such as undisclosed factoring and bulk factoring are analysed. The research is based on a comprehensive bibliographical analysis of doctrines in Portuguese and Spanish, as well as relevant case law. The results highlight the diversity of factoring modalities available globally, with regional and sectoral particularities. This work contributes to clarifying the terminology and functionality of the factoring contract, offering a detailed overview of its practical applications and legal implications.